Polycystic ovary syndrome: the competence of a family doctor - V.V. Artyomenko; V.I. Velychko; D.O. Lahoda; N.M. Nastradina; K.O. Nitochko (Publishing House TRILIST, 2023)
Polycystic ovary syndrome (PCOS) is one of the most common diseases in the population of women of reproductive age. Due to the wide range of symptoms, PCOS can affect different body systems and be one of the comorbid diseases during a woman's life. A family doctor may suspect the diagnosis of PCOS in a woman of reproductive age if there are symptoms of menstrual irregularities and/or concomitant symptoms of androgen excess, namely acne, hirsutism, etc. According to the Rotterdam criteria, the diagnosis of PCOS can be established if there are two of the following three criteria: hyperandrogenism (established clinically or biochemically), irregular menstrual cycle (< 9 cycles per year or interval between cycles > 35 days) and polycystic ovaries at the ultrasound study (> 12 antral follicles in one ovary and/or ovarian volume > 10 cm2). Differential diagnosis of PCOS requires the exclusion of other diseases, most often these are: pregnancy, thyroid gland dysfunction, hyperprolactinemia, Cushing's syndrome; less often - congenital hyperplasia of the adrenal glands and androgen-secreting tumors. Anthropometric research is also one of the examination of patients with PCOS. First-line therapy for obese women with PCOS is lifestyle modification through behavioral therapy, moderate physical activity, and healthy eating habits. In addition to lifestyle modification, PCOS treatment should be multitargeted to match each patient's phenotype, symptoms, personal goals, and expectations, such as desire to become pregnant. Screening for diabetes, dyslipidemia, hypertension, anemia, and vitamin D deficiency is important in the management of PCOS patients. All patients with a severe or rapidly progressive course, or those with testosterone levels greater than twice the upper limit of normal, should be referred to an endocrinologist or gynecologist to rule out other causes of the condition.